The Urgency of Synchronizing Regulations on the Concept of State Assets in State-Owned Enterprises - Anak Agung Anggy Tryeza Purnama Ningrum; I Putu Puja Astawa (International Journal Labs, 2026)
The main issue raised in this paper is the urgency of synchronizing regulations on the concept of state assets in state-owned enterprises. It examines the synchronization of legal provisions concerning the status of assets owned by state-owned enterprises (SOEs), as regulated under various laws. The disharmony in these legal provisions regarding the status of SOE assets as part of state finances has resulted in legal uncertainty. The State Finance Law, the State Treasury Law, and the Law on Audit of the Management and Accountability of State Finances stipulate that state assets separated and placed in SOEs are considered part of state finances. Meanwhile, the SOE Law and its Third Amendment stipulate that state assets separated and placed in SOEs do not constitute state finances. This ambiguity regarding the status of SOE assets—whether they form part of state finances or belong to the SOEs as legal entities—gives rise to legal uncertainty. From the perspective of legal justice, treating SOE assets as state finances contravenes the principle of proportional equality, as it implies that the State does not recognize SOEs as private legal entities. Furthermore, from the standpoint of legal utility, the continued view that SOE assets are part of state finances creates confusion, particularly since SOE capital is not entirely sourced from state assets but also includes shares held by public investors. Therefore, it is imperative for the Government and the House of Representatives to revise the State Finance Law, the State Treasury Law, and the Law on Audit of the Management and Accountability of State Finances.